Assessment of errors and misused statistics in dental research. - Kim JS; Kim DK; Hong SJ; Kim, Jee Soo Jay; Kim, Dong-Kie; Hong, Suk Jin (International Dental Journal, 2011)
Objectives:   The goal of the study is to assess the level of misused statistics or statistical errors in dental research, and identify the major source of statistical errors prevalent in dental literature.Methods:   A total of 418 papers, published between 1995 and 2009, was randomly selected from 10 well established dental journals. Every paper in the sample underwent careful scrutiny for the correct use of statistics. Of these, there were 111 papers for which we were unable to judge whether or not the use of statistics was appropriate, due to insufficient information presented in the paper; leaving 307 papers for this study. A paper with at least one statistical error has been classified as 'Misuse of statistics', and a paper without any statistical errors as 'Acceptable'. Statistical errors also included misinterpretation of statistical analytical results.Result:   Our investigation showed that 149 were acceptable and 158 contained at least one misuse of statistics or a statistical error.Conclusion:   This gave the misuse rate of 51.5%, which is slightly lower than that reported by several studies completed for the medical literature.